Diagnosis of translocation t(12;17)(q24.1;q25) in a family - Guapi nauñay, Victor (2025)
Reciprocal translocations occur as a consequence of breakage in non-homologous chromosomes with exchange of the detached segments, characterized by the absence of loss of genetic material as a whole. This research aimed to evaluate the effects of the apparently balanced translocation in a family. A 5-year-old female patient presented a broad and prominent forehead, ocular hypertelorism, with low-set and backward-rotated earlobes, hypoplasia of the earlobes, low nasal bridge, anteverted nostrils, wide mouth, micro and retrognathia. Among the antecedents, she recorded a marked delay in neurodevelopment. The conventional cytogenetic study reported 46, XX,der(17), from the maternal reciprocal balanced translocation with a result of 46,XX,t(12;17) (q24.1;q25)mat as in the maternal grandmother. The cytogenetic method of fluorescence in situ hybridization in blood lymphocytes showed the presence of three signals for chromosome 12q24.1. The findings suggest that chromosomal rearrangements including apparently balanced familial reciprocal translocations have a negative effect on the clinical phenotype and neurodevelopment.